A simple method for amateur investors to analyze covered call options - Samsa, Greg (Archives of Business Research, 2020)
We describe a simple method which amateur investors can use to analyze covered calls. The most basic version is based on the formula for the expectation of a truncated Gaussian distribution, and it can be generalized to accommodate other assumptions. This approach might be especially considered during a time of market overvaluation, such as the present. During such times, investors should shift their preferences toward writing deep-in-the-money covered calls, which provide a greater margin of safety while monetizing the (probably optimistic) expectations of other market participants regarding future returns.